The Role of Traditional Communities in Managing Natural Resources - Permana, Raditya (Law Research Review Quarterly, 2015)
Ahead of the plenary as President of the Republic of Indonesia, Susilo Bambang Yudhoyono, on September 1, 2014, issued an issue of Enhancing National Competitiveness in the context of facing the ASEAN Economic Community. The President instructs all state officials and their staff to take the necessary steps in accordance with their respective duties, functions and authorities in a coordinated and integrated manner to enhance national competitiveness and prepare for the implementation of the ASEAN economic community which will begin in 2015 .